Analisis Pengaruh Konsumsi Buah Bit Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Trimester III - Liananiar; Fatma Sylvana Dewi Harahap; Elvi Era Liesmayani (HEALTH CARE : JURNAL KESEHATAN, 2020)
Beetroot is able to stimulate, build, cleanse, and be able to strengthen the circulatory system and red blood cells so that it can carry body substances and can prevent the lack of red blood cells in the body. Hemoglobin is part of the blood that contains iron-rich protein. The third trimester of pregnancy is the last 3 months period of pregnancy which starts on the 28th week until the 40th week. The results of a survey conducted on 50 pregnant women obtained results that examined hemoglobin, 30 of 50 pregnant women obtained Hb results of ≥11 gr / dL. The purpose of this study was to analyze the effect of factors affecting Hb levels in third trimester pregnant women in the UPTD of Jeumpa District Health Center Bireuen District in 2019. The design used in this study is True Experimental Design with the Pretest-Posttest Desaign Control Group approach. The population in this study were 50 third trimester pregnant women with a sample of 24 people, 12 respondents for the experimental group and 12 respondents for the control group. Based on the analysis of paired t-test test in the experimental group showed that the value of p value is 0.002, this means p <0.05, then there is a significant difference in hemoglobin levels between the hemoglobin level pre-test and hemoglobin level post-test by consuming beetroot. For health workers to provide information on hemoglobin levels before and after giving beetroot to pregnant women so that it can be used as a basis for decision making in an effort to increase Hb levels and prevent the occurrence of anemia, a reference to making a product of beetroot extracts.